State-Dependent and Bandwidth-Specific Effects of Ketamine and Propofol on Electroencephalographic Complexity in Rats - Brito, Michael A.; Li, Duan; Mashour, George A.; Pal, Dinesh (Frontiers in Systems Neuroscience, 2020)
There is an ongoing debate as to whether ketamine anesthesia suppresses neurophysiologic complexity at doses sufficient for surgical anesthesia, with previous human studies reporting surrogates of both suppressed and preserved levels of cortical complexity. However, these studies have not assessed cortical dynamics in higher gamma frequencies, which have previously been demonstrated to correlate with the level of consciousness during anesthesia. In this study, we used Lempel-Ziv complexity (LZc) to characterize frontal and parietal electroencephalographic complexity (0.5-175 Hz, 0.5-55 Hz, 65-175 Hz) before, during, and after ketamine or propofol anesthesia in rat. To control for the potential influence of spectral changes in complexity estimation, LZc was normalized with phase-shuffled surrogate data. We demonstrate that ketamine and propofol anesthesia were characterized by significant reduction in broadband (0.5-175 Hz) LZc. Further analysis showed that while the reduction of LZc during ketamine anesthesia was significant in 65-175 Hz range, during propofol anesthesia, a significant decrease was observed in 0.5-55 Hz bandwidth. LZc in broadband and 0.5-55 Hz range showed significant increase during emergence from ketamine anesthesia. Phase-shuffled normalized LZc revealed that 1) decrease in complexity during ketamine and propofol anesthesia – not increase in complexity during emergence – were dissociable from the influence of spectral changes, and 2) reduced LZc during ketamine anesthesia was present across all three bandwidths. Ketamine anesthesia was characterized by reduced complexity in high gamma bandwidth, as reflected in both raw and phase-shuffled normalized LZc, which suggest that reduced high gamma complexity is a neurophysiological feature of ketamine anesthesia.